O Leitor Incomodado: Ciência e Literatura no Romance Saturday de Ian McEwan - Neves, Marco (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
In this article, I discuss the confrontation between science and literature on the literary stage created by Ian McEwan in his novel Saturday. This novel is a form of intellectual intervention through an exercise of provocation to the reader. It is, in essence, an attempt to lead the reader out of his usual position, which requires some discomfort while reading. This discomfort is created through the use of technical-scientific language and the struggle between discourses on the stage of the novel, as theorized by Bakhtin. The critical discussion of this work will allow us to briefly illuminate the complex relationship between Literature and Science.